Contribution of natural uranium isotopes to the study of groundwater flow - Mancini, Luís Henrique (2021)
Uranium is a lithophile element that is preferentially concentrated in acid rather than basic/ultrabasic igneous rocks. Its average crustal abundance corresponds to 2.5 μg/g, composed of two primary isotopes, 238U (~99.3%) and 235U (~0.7%). Despite the technological importance of 235U, as it is the fissile isotope that is the basis of nuclear energy production, it appears that its contribution as a natural source of radioactivity is small, since the specific activity of 238U is about 20 times greater than 235U. Isotopes 238U and 235U are progenitors of radioactive decay series, the greater number of descendants corresponding to 238U, many of which possessing a long half-life, such as 234U formed in the 238U decay series from the following sequence: 238U (4.49 Ga, α) → 234Th (24.1 days, β-) → 234Pa (1.18 min, β-) → 234U (248 ka, α) →... Both 238U and 234U are emitters of alpha particles and, in groundwater, the assessment of the extent of radioactive imbalance between these uranium isotopes has allowed the development of numerous studies of hydrogeological interest since the 1960’s. The main mechanisms that explain such disequilibrium are the 234U selective leaching relatively to 238U from the crystalline lattice of minerals and alpha recoil that introduces 234Th into the liquid phase, which forms 234Pa by beta decay, radionuclide that produces 234U, also by beta decay, causing 234U-enrichment in groundwaters, i.e., 234U/238U activity ratios greater than unity. These ratios, together with the dissolved uranium concentration, have been extensively utilized in hydrological applications, such as those described in this paper.